A Simple Approach for Deciding When to Invest - Berk, Jonathan B (American Economic Review, 1999)
A straightforward generalization of the simple net present value rule that correctly predicts when to invest in two classes of projects that can be delayed is derived. The first class consists of projects for which the option to delay derives its value exclusively from uncertainty about interest rates. It is shown that the optimal rule for investing in such projects is to simply multiply the discount rate of the project by the ratio of the mortgage rate to the riskless rate and then use this new rate as the discount rate in a standard net present value analysis. The other class of investment opportunities that is considered is the firm's option to expand. It is shown that it is only optimal for the firm to expand when a particular call option on the firm's stock has no time value. The fact that mortgage bonds (in the form of GNMAs) and stock options are actively traded implies that these rules have potentially important practical and empirical value. Besides their simplicity, the rules have the added advantage that they do not depend on a maintained assumption on the dynamics of interest rates in the economy.